TATA RUANG DAN KERUANGAN KOMPLEKS MAKAM KOTAGEDE (SINKRETISASI BUDAYA JAWA DENGAN ISLAM) - Riswinarno, Riswinarno (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2018)
This article explores the tombs in the compound of mosque and Islamic Mataram cemetery in Kotagede. The object used for the research is the tomb complex which is located behind the Kotagede mosque. The main figure buried in the cemetery is Panembahan Senopati and some of his close relatives. The research is conducted due to the pattern of placement and arrangement of the tombs which is interesting as an object of study. Certain patterns are found in the use of space in the tomb complex, both horizontally and vertically. Further studies are needed to see whether the pattern have to do with the concept of habluminallah and habluminanas? Certainly, these patterns could be the influence of Islam in the Javanese culture. This is quite understandable since the tomb concept maker is the main figure of Islamic Mataram kings, i.e., Panembahan Senopati.)